The Relationships between ESG Responsibility, Earnings Management, and Tax Aggressiveness: Evidence of the Halo Effect from Indonesia - Erni Ekawati (Journal of Indonesian Economy and Business)
Introduction/Main Objectives: Sustainable firms should develop competitiveness by seeking interconnections between financial and non-financial goals. This research investigates the halo effect to shed light on the motives behind environmental, social, and governance (ESG) responsibility and tax aggressiveness engaged in by the firms dealing with real earnings management (REM). Background Problems: Do higher ESG scores improve corporate value due to corporate credibility and ethical practices, or due to the motive of doing good to cover up irresponsible practices? Novelty: Only a few studies have investigated the motivation of Indonesian companies in carrying out ESG, associated with REM and tax aggressiveness to test for a halo effect. Research Methods: This study is based on a sample of manufacturing companies listed on the Indonesia Stock Exchange between 2015 and 2019. Panel data regression models are used in testing the hypotheses. Finding/ Results: ESG scores have a positive effect on market value. The halo effect is present in manufacturing firms practicing REM. Firms entering into REM have significantly higher ESG scores. REM has a negative effect while ESG scores have a positive effect on tax aggressiveness. Conclusion: ESG scores could increase firms’ value. However, the presence of the halo effect results in higher ESG scores for firms engaging in REM. The REM activity prevents firms from aggressive tax planning, while governance responsibility encourages them to do so. The halo effect opens up the opportunity to engage in REM and tax aggressiveness. Thus, the government requires scrutiny considerations in order to avoid the unfavorable side effects of ESG enforcement.